THE ROLE OF THE WORLD BANK IN THE ECONOMIC DEVELOPMENT OF PAKISTAN: A CRITICAL ANALYSIS - Mekhraj Khan; Saif Ali Khan; Abbas Yaqoob (International Journal of Contemporary Issues in Social Sciences, 2024)
Pakistan, upon gaining independence, faced significant economic challenges stemming from its fragile economic base. Over the years, the country has encountered a mixed record of economic development. This Study explores the role played by the World Bank in Pakistan’s economic development, with a particular focus on industrial development and the challenges encountered post-independence. Purpose of the Study: This study aims to comprehensively examine the impact and contributions of the World Bank towards the economic progress of Pakistan. By delving into the initial challenges faced by the country and analyzing the subsequent shifts in economic policies, it seeks to understand the efficacy of the World Bank’s interventions in fostering industrial growth and overall economic stability. A qualitative research design has been used in this study, and adopted for this study involves a thorough review of existing literature, historical data, and policy documents related to Pakistan’s economic development and its interactions with the World Bank. Despite periods of promising economic performance, Pakistan has consistently grappled with fiscal and external imbalances, high unemployment, and persistent poverty. While the World Bank’s interventions have shown some signs of improvement in macroeconomic indicators, sustained progress remains elusive. Therefore, it is recommended that future collaborations between Pakistan and the World Bank focus on implementing targeted reforms addressing structural issues, promoting inclusive growth, and enhancing institutional capacity to ensure long-term sustainable development.